2015
DOI: 10.1177/0950017014559267
|View full text |Cite
|
Sign up to set email alerts
|

Gender, work orientations and job satisfaction

Abstract: This article studies the gender gap in job satisfaction and argues that the observed gender difference is a consequence of the heterogeneity in work orientations between men and women. Using data from the 2006 Skills Survey, the analysis yields three major findings. The first shows that women, either in full-time or part-time employment, report significantly higher levels of job satisfaction than men. Secondly, work orientations are closely associated with one's job satisfaction and their relationships vary si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
6
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 31 publications
3
71
6
3
Order By: Relevance
“…This measure has been used previously (Clark, Masclet and Villeval, 2008;Bjornstrom, 2011;Kifle, 2013;Latif, 2015;Zou, 2015) and captures income comparisons against the 'average' group member:…”
Section: Distance From the Meanmentioning
confidence: 99%
“…This measure has been used previously (Clark, Masclet and Villeval, 2008;Bjornstrom, 2011;Kifle, 2013;Latif, 2015;Zou, 2015) and captures income comparisons against the 'average' group member:…”
Section: Distance From the Meanmentioning
confidence: 99%
“…This seems a plausible explanation since the collected samples in the present paper have high frequencies of higher academic levels, which are expected to be associated with higher job status. Zou [140] reported that when work orientations are taken into account, job satisfaction differences among women and men are eliminated. Also, there is evidence that women and men are similar in the crossover and spillover dynamics regarding job satisfaction, job insecurity, own family and partner's family life satisfaction [141].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MI method is very popular in social sciences and medical studies. Examples in the field of medicine include (Burton et al 2007;van Buuren et al 1999;Newgard et al 2018;Pettersson et al 2018;Sterne et al 2009;Troyanskaya et al 2001) and (Alegria et al 2004;Allison 2000;König et al 2018;Love et al 2018;Phan et al 2016;Roth 1994;Zou 2015) for social sciences. Very few applications have been found in transport research with exceptions being (Chiou et al 2014;Henrickson et al 2015;Li et al 2015;Tang et al 2015) that uses MI method to fill the missing data in traffic flows or loop detectors.…”
Section: Literature Reviewmentioning
confidence: 99%